How thin can you go? Performance of thin copper and aluminum RF coil conductors. Issue 4 (15th October 2020) - Barta, Radim; Volotovskyy, Vyacheslav; Wachowicz, Keith; Fallone, B. Gino; De Zanche, Nicola
Abstract : Purpose: To evaluate the impact of emerging conductor technology on RF coils. Performance and resulting image quality of thin or alternate conductors (eg, aluminum instead of copper) and thicknesses (9‐600 μm) are compared in terms of SNR. Methods: Eight prototype RF coils (15 cm × 15 cm square loops) were constructed and bench‐tested to measure quality factor. The coils used 6‐mm‐wide conducting strips of either copper or aluminum of a few different thicknesses (copper: 17, 32, 35, 127, 600 μm; aluminum: 9, 13, 20, 127 μm) on acetate projector sheets for backing. Corresponding image SNR was measured at 0.48 tesla (20.56 MHz). Results: The coils spanned a range of unloaded quality factors from 89 to 390 and a fivefold range of losses. The image SNRs were consistent with the coils' bench‐measured efficiencies (0.33‐0.73). Thin aluminum conductors (9 μm) led to the highest reduction in SNR (65% that of 127 μm copper). Thin copper (<32 μm) conductors lead to a much smaller decrease in SNR (approximately 10%) compared to 127 μm copper. No performance difference was observed between 127 μm thick copper and aluminum. The much thicker 600 μm copper bars only yield a 5% improvement in SNR. Conclusion: Even at 0.48 tesla, copper RF coil conductors much thinner than those in conventional construction can be used while maintaining SNR greater than 50% that of thick copper. These emerging coil conductor technologies enable RF coil functionality that cannot be achieved otherwise.